2021
DOI: 10.1039/d1sc04748e
|View full text |Cite
|
Sign up to set email alerts
|

Radical–anion coupling through reagent design: hydroxylation of aryl halides

Abstract: The design and development of an oxime-based hydroxylation reagent, which can chemoselectively convert aryl halides (X = F, Cl, Br, I) into phenols under operationally simple, transition-metal-free conditions is described....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 63 publications
3
14
0
Order By: Relevance
“…[12b,c] Because the intermediate containing the (2c,3e) half-bond has a much higher reduction potential than other species present in the reaction, it can be selectively oxidized by a relatively mild oxidant, for example, molecular oxygen. Additional examples of redox chains mediated by highly reducing upconverted radical anion intermediates continue to appear, for example, a photochemical thiol-yne click reaction reported by Ananikov et al, [15] hydroxylation reaction of aryl halides with oximes by James et al [16] and a number of other transformations. [17] Recently, Jui and co-workers have demonstrated a facile transformation of formate into upconverted CO 2 *À species (a traditionally challenging reductant to make, E 1/2 = À 2.2 V vs. SCE) capable of reducing a broad range of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[12b,c] Because the intermediate containing the (2c,3e) half-bond has a much higher reduction potential than other species present in the reaction, it can be selectively oxidized by a relatively mild oxidant, for example, molecular oxygen. Additional examples of redox chains mediated by highly reducing upconverted radical anion intermediates continue to appear, for example, a photochemical thiol-yne click reaction reported by Ananikov et al, [15] hydroxylation reaction of aryl halides with oximes by James et al [16] and a number of other transformations. [17] Recently, Jui and co-workers have demonstrated a facile transformation of formate into upconverted CO 2 *À species (a traditionally challenging reductant to make, E 1/2 = À 2.2 V vs. SCE) capable of reducing a broad range of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…been debated, with several radical-based alternatives proposed. [9] Inspired by this work, and our recent study, [10,11] in which we postulated that oxime anion 4 can substitute aryl halides 5 through an electron-catalysed radical-nucleophilic substitution (S RN 1) chain mechanism (Scheme 1c), [12,13] we sought to determine if a general denitrative hydroxylation protocol using our designed reagent could be realised. We rationalised that a broad range nitroarenes may also be substituted by an S RN 1 mechanism if aryl radicals can be formed via the fragmentation of nitroarene radical-anions.…”
mentioning
confidence: 99%
“…[74b] Both secondary and tertiary amides (134) bearing diverse functional groups were obtained in moderate to good yields. Additionally, the authors demonstrated a one-pot procedure to obtain amides directly from aldehydes (133), amines and TMSCN via in situ generation of α-aminonitriles (132). Radical scavenging experiments indicated that an anionic pathway was involved in the CÀ CN bond cleavage process.…”
Section: Amidation Applying New Alternative Strategiesmentioning
confidence: 99%